Whispered history of art - Filliou, Robert 1926-1987; Higgins, Dick 1938-1998; Maciunas, George 1931-1978; Garghetti, Fabrizio 1939- (Slowscan, 2015)
Robert Filliou (1926-1987) was a French poet, writer and artist affiliated with Nouveau réalisme and Fluxus. He became a member of the French Communist Party during the German occupation when he was 17 years old and travelled to the US two years after the liberation. There he took a degree in economics. After having worked for the Coca Cola company in LA and having been granted a double French-American nationality, Filliou held the position of consultant for the UN and as such was sent to Korea for three years. Filliou abandoned economics and turned towards art in the late 1950s when he got in touch with the Nouveaux réalistes – Daniel Spoerri in the first place – and George Brecht. His first visual work, 'Collage of the Immortal Death of the World', came about in 1960. Filliou conceived the celebration of Art's Birthday' in 1963. He claimed that 1,000,000 years ago there was no art at all until one day, on 17 January to be precise, art was born when someone dropped a dry sponge into a bucket of water. Art’s birthday – which, by the way, happened to coincide with Filliou’s own – saw its first public celebration on 17 January 1973 in Aachen, Germany and in Paris, France. Filliou was awarded the Schwitters prize of the city of Hannover in 1982. Together with his wife Marianne Staffels he withdrew for 3 years, 3 months and 3 days in a Buddhist centre in les Eyzies, France. He died in a monastery in the same town in 1987. Filliou's 'Whispered History of Art', now released on vinyl as Slowscan vol. 30, is a Fluxus mythology about the origin of art. The playful and humorous lecture was recorded by Ondine Fiore at the New Wilderness Studio, New York in December 1977 and is introduced by Dick Higgins. Courtesy Filliou recording: Archivio Francesco Conz. Verona.
Titel von Coverrücken. - 12" black vinyl in offset printed sleeve, recorded by Ondine Fiore at the New Wilderness Studio, New York, December 1977
186 copies
Keywords: Filliou, Robert -- 1926-1987 -- Whispered art history; Schallplatte